Lymphocyte depletion and repopulation after chemotherapy for primary breast cancer. Issue 1 (December 2016) - Verma, Rashmi; Foster, Ruth; Horgan, Kieran; Mounsey, Katherine; Nixon, Helen; Smalle, Natuley; Hughes, Thomas; Carter, Clive
Abstract Background Approximately 30 % of breast cancer patients receive chemotherapy, yet little is known about influences of current regimens on circulating lymphocyte levels and phenotypes. Similarly, clinico-pathological factors that modify these influences, and implications for future immune health remain mainly unexplored. Methods We used flow-cytometry to assess circulating lymphocyte levels and phenotypes in 88 primary breast cancer patients before chemotherapy and at time-points from 2 weeks to 9 months after chemotherapy completion. We examined circulating titres of antibodies against pneumococcal and tetanus antigens using ELISAs. Results Levels of B, T and NK cells were significantly reduced 2 weeks after chemotherapy (p < 0.001). B cells demonstrated particularly dramatic depletion, falling to 5.4 % of pre-chemotherapy levels. Levels of all cells recovered to some extent, although B and CD4+ T cells remained significantly depleted even 9 months post-chemotherapy (p < 0.001). Phenotypes of repopulating B and CD4+ T cells were significantly different from, and showed no sign of returning to pre-chemotherapy profiles. Repopulating B cells were highly depleted in memory cells, with proportions of memory cells falling from 38 % to 10 % (p < 0.001). Conversely, repopulating CD4+ T cells were enriched in memory cells, which increased from 63 % to 75 % (p < 0.001). Differences in chemotherapy regimen and patient smoking were associated with significant differences in depletion extent or repopulation dynamics. Titres of anti-pneumococcal and anti-tetanus antibodies were both significantly reduced post-chemotherapy and did not recover during the study (p < 0.001). Conclusion Breast cancer chemotherapy is associated with long-term changes in immune parameters that should be considered during clinical management.